An examination of human capital dimensions that has an influence on knowledge management practices to innovate : a case study of the State Security Agency (SSA) - Timana, Lovely Nkomo (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.